Bottom boundary layer oxygen fluxes during winter on the Oregon Shelf - Reimers, Clare E.; Fogaren, Kristen E. (Journal of Geophysical Research - Oceans, 2021)
In this study, lander-based eddy covariance measurements made 30 cm above a sandy seafloor are combined with ocean-observing and ship-based measurements to evaluate magnitudes of oxygen fluxes within the bottom boundary layer (BBL) during winter on the Oregon shelf. The total oxygen fluxes observed at a mid-shelf station were −12.3 ± 7.6 and −18.6 ± 16.9 mmol m−2d−1 during February 2018 and January 2019 deployments, respectively, and −51.8 ± 34.9 mmol m−2d−1 during a deployment on the inner shelf in January 2019. These mean (±SD) flux derivations are greater than fluxes determined previously at nearly the same locations during the summer upwelling season, which points to the activation of benthic respiration by winter wave-dominated BBL dynamics. To determine the direct flux contributions (or potential bias) at wave frequencies, a phase-based method of spectral decomposition was applied to separate wave-induced and turbulence-induced components of velocity and dissolved oxygen time-series. This approach identified 25.4, 18.6, and 23.3% of the average total EC oxygen fluxes from the three deployments as carried by waves or possibly turbulence stretched by waves. Additionally, we observed evidence of large waves regularly resuspending sediments and transporting entrained particles past the EC sensors. We apply this evidence to infer that wave frequencies must also contribute significantly to the real spectral domain of benthic oxygen fluxes and that the total fluxes of this study reflect elevated oxygen consumption rates without artifacts. This assessment may not be true for all data sets and may be dependent on wave properties and the quality and treatment of the measurements.
Keywords: bottom boundary layer; eddy covariance; Oregon shelf; oxygen fluxes; turbulence; waves